Haemato-Biochemical Alterations in Dogs with Vomition - Khanduri, Rimjhim; Raval, Sunant K.; Dave, Keshank; Rao, Neha (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Vomition is a common clinical presentation in small animal practice and may be associated with gastrointestinal and systemic diseases. Fifty cases of vomition in dogs were studied at Veterinary Clinical Complex of the College in Anand during the period of six months for clinical and haemato-biochemical alterations in comparison to 8 normal healthy dogs. Among 50 dogs, the incidence of vomiting possibly due to Parvo viral infection, pyometra, renal disorders, encylostoma infection, pseudo-pregnancy, hepatic disorders, thrombocytopenia, neutrophilia and dietary abnormalities was in 44.0, 2.0, 14.0, 14.0, 2.0, 4.0, 2.0, 14.0 and 4.0 % cases, respectively. The levels of PCV, TLC and basophils were increased significantly (p <0.05) with decreased Hb in dogs suffering with vomiting as compared to healthy control group. The serum biochemical examinations revealed significantly (p <0.05) decreased mean serum albumin concentration and increased serum creatinine, BUN, ALT and AST values in dogs with vomiting as compared to healthy control group. However, TEC, lymphocyes, neutrophils, eosinophils, monocytes counts and serum total protein did not vary significantly between vomiting and healthy dogs.